2010
DOI: 10.1002/spip.409
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of CMMI with expanding company size for small‐ to medium‐sized enterprises

Abstract: In this article we show how the results from software process appraisals of ten small‐ to medium‐sized software development enterprises demonstrate that as companies become larger they naturally use an increasing number of practices within the Capability Maturity Model Integration (CMMI®). The companies involved in this study had no CMMI® experience prior to this work. We identify those practices that tend to be best followed by both small‐ and medium‐sized enterprises and those that tend to be introduced as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Like the small team within a larger company, small shops have little need for elaborate plans, change management procedures or document-based coordination and communication in general [14,15]. However, a small team working in a large company often has access to resources not found in the small company setting.…”
Section: Small Shop Software Developmentmentioning
confidence: 96%
See 3 more Smart Citations
“…Like the small team within a larger company, small shops have little need for elaborate plans, change management procedures or document-based coordination and communication in general [14,15]. However, a small team working in a large company often has access to resources not found in the small company setting.…”
Section: Small Shop Software Developmentmentioning
confidence: 96%
“…designed around frequent and incremental deliveries, and a workable channel for rapid customer feedback for revised requirements [3]. The family of agile software development methods, which research has shown to be suited to the small team environment, seems to fit these conditions of the small shop software shop [14,15].…”
Section: Small Shop Software Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…According to Barry Boehm , there are three things that can improve project efficiency: work faster, work in smarter way or work less. Clearly, reuse is an optimal alternative for the last issue, although it may be the answer to all three.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%